2012
DOI: 10.3354/dao02519
|View full text |Cite
|
Sign up to set email alerts
|

Denman Island disease (causative agent Mikrocytos mackini) in a new host, Kumamoto oysters Crassostrea sikamea

Abstract: Mikrocytos mackini, causative agent of Denman Island disease in Pacific oystersCrassostrea gigas and other oyster species, was found in 2011 in a previously unreported host, the Kumamoto oyster C. sikamea, in Humboldt Bay, California, USA. The detection was also the first reported finding of M. mackini in California. Prevalence was estimated as high as approximately 27% from pooled samples analyzed by PCR. Higher prevalence appeared related to longer residence time in the bay and somewhat colder than typical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Although it is known that submergence (increasing water levels) can inhibit plant growth [4, 12, 15, 27, 32], our study shows that the effects of water level are dependent on fluctuation frequency. Plants that are able to escape levels of submergence that are disadvantageous to their growth can continue to accumulate biomass.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although it is known that submergence (increasing water levels) can inhibit plant growth [4, 12, 15, 27, 32], our study shows that the effects of water level are dependent on fluctuation frequency. Plants that are able to escape levels of submergence that are disadvantageous to their growth can continue to accumulate biomass.…”
Section: Discussioncontrasting
confidence: 56%
“…While rising water levels submerge plants, falling water levels indicate water scarcity, creating water stress for plants. Many experiments have been performed to study the effects of submergence on riparian plants, reporting various morphological and physiological adjustments to submergence [1218]. Other studies have addressed the response of plants to submergence and de-submergence [9, 19], as well as the effects of the amplitude of water level fluctuation [5, 2023].…”
Section: Introductionmentioning
confidence: 99%
“…This parasite was responsible for Denman Island disease in the wild and cultured Pacific oyster Crassostrea gigas Thunberg, 1793 in British Columbia, Canada, where it induced severe oyster mortalities [ 8 ]. It could naturally affect other oysters, such as the Olympia oyster Ostrea lurida Carpenter, 1864 [ 10 ] or the Kumamoto oyster Crassostrea sikamea Amemiya, 1928 [ 11 ]. Since its detection, the range extension of this parasite has been limited to the west coast of North America, in Canada and the USA [ 9 , 11 – 13 ]; it has never been detected in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…It could naturally affect other oysters, such as the Olympia oyster Ostrea lurida Carpenter, 1864 [ 10 ] or the Kumamoto oyster Crassostrea sikamea Amemiya, 1928 [ 11 ]. Since its detection, the range extension of this parasite has been limited to the west coast of North America, in Canada and the USA [ 9 , 11 – 13 ]; it has never been detected in Europe. Because of its potential impact on oyster farming, this parasite is regulated in Europe and surveillance is implemented in different European countries in order to prevent its introduction.…”
Section: Introductionmentioning
confidence: 99%
“…Re cently, it has also been detected in Washington State (USA) (Bower 2010, Abbott et al 2011) and has been found to infect C. sikamea from California (USA) (Elston et al 2012). M. mackini is included in the group of microcell parasites of molluscs due to its small size (2−4 µm), together with haplosporidian parasites of the genus Bonamia.…”
Section: Contribution To Dao Special 7 'Microcell Parasites Of Molluscs'mentioning
confidence: 99%